2015
DOI: 10.1049/iet-gtd.2014.0659
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge representation and general Petri net models for power grid fault diagnosis

Abstract: This study deals with the idea that comprehensive knowledge representation should be established for fault diagnosis. Sufficient grid fault information including the network topology and protection knowledge are used with a diagnostic algorithm. In this way, the fault diagnosis programme not only facilitates accurate judgment of fault sections for which many kinds of information are available but also optimises knowledge to simplify the fault diagnosis method. Petri nets are used for logical reasoning on the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…• A novel system design of a load-balance system integrated with the legacy LV system and urban microgrids is proposed. This is validated in Petri nets, emphasizing the novel form of encapsulating combined algorithms, evidenced by hierarchy levels of integration [43]; •…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…• A novel system design of a load-balance system integrated with the legacy LV system and urban microgrids is proposed. This is validated in Petri nets, emphasizing the novel form of encapsulating combined algorithms, evidenced by hierarchy levels of integration [43]; •…”
Section: Introductionmentioning
confidence: 99%
“…The procedure is based on the use of identification algorithms and load transfer management, aiming at minimizing current and load consumption [38] or voltage and load [27]. In both cases, the voltage and load equilibrium state in the grid phases is guaranteed; however, the switching choice is based only on current load consumption of consumers' units, disregarding the imbalance level and the future states of load consumption, which could contribute to the robustness of the system to eventual consumption peaks and to the durability of the load stability over time.By contrast, it has been observed that the use of Petri nets (PNs) in complex systems is quite broad [39], due to its formal modeling, simulation and property verification capabilities [40][41][42], which allows development and verification of intelligent algorithms for control and supervision of application in smart grids [43,44]. The formal verification of routine flow allows evaluation of incidences, conflicts, deadlocks, loops, and reachability [45] of all stages and subroutines, as well as evaluation of inviolable flows and cycles of the algorithm in all its hierarchical levels [46], and also the automatic integration workflow with the control and supervision systems of an urban microgrid [47].Thus, the use of PNs can contribute to the solution of the lack of automation in the operational procedures of load balancing in urban microgrids and especially in the LV grid [48], such as in the case of the legacy Brazilian LV distribution grid [15], with partially automated flows and manual methods without automatic full flow with the central supervisory system.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This power grid fault diagnosis system has been applied in a digital substation in Xingguo, China. Wang and Chen [15] proposed a Petri net that combines the power grid topology with PR information to render the fault diagnosis model. An ANN-based condition monitoring approach using data from SCADA has also been proposed [16].…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced with the well-established fuzzy logic, the fuzzy Petri nets (FPNs) [15][16][17][18][19][20], superior to the traditional Petri nets [21,22], are capable of modeling inexactness and uncertainties. Graphical FPN models are built in [16] for fault section identification, but the model structure is not optimized and the matrix execution algorithm is not addressed.…”
Section: Introductionmentioning
confidence: 99%